Bacterial anti-adhesive and pH-induced antibacterial agent releasing ultra-thin films of zwitterionic copolymer micelles. (August 2016) - Onat, Bora; Bütün, Vural; Banerjee, Sreeparna; Erel-Goktepe, Irem
Graphical abstract: Abstract: We report on preparation of substrates with dual function coatings, i.e. bacterial anti-adhesive and antibacterial agent releasing polymer films of zwitterionic block copolymer micelles (BCMs). BCMs were obtained by pH-induced self-assembly of poly[3-dimethyl (methacryloyloxyethyl) ammonium propane sulfonate- b -2-(diisopropylamino)ethyl methacrylate] (βPDMA- b -PDPA), resulting in BCMs with zwitterionic βPDMA-coronae and pH-responsive PDPA-core. These zwitterionic BCMs were then used as building blocks to construct mono- and multi-layer films. We found that the number of layers in the film was critical for the anti-adhesive property and 3-layer films were the most anti-adhesive against a model Gram-positive bacterium, Staphylococcus aureus . Antibacterial activity could be introduced to the films by loading Triclosan into βPDMA- b -PDPA micelles. Triclosan containing films were effective against Triclosan-sensitive Staphylococcus aureus specifically at moderately acidic conditions due to pH-induced disintegration of the micellar core blocks and release of Triclosan from the surface. Three-layer films also exhibited anti-adhesive property at physiological pH against a model Gram-negative bacterium, Escherichia coli . At moderately acidic pH, the coatings showed a contact antibacterial effect against an isolate of Escherichia coli with low sensitivity to Triclosan only when micellar cores were loaded with Triclosan. Such dual function films can be promising to combat biofouling at the non-homogeneous and/or defective parts of an anti-adhesive coating. Moreover, considering the moderately acidic conditions around an infection site, these multilayers can be advantageous due to their property of pH-induced antibacterial agent release. Statement of Significance: This study presents preparation of substrates with dual function ultra-thin coatings of zwitterionic block copolymer micelles which show bacterial anti-adhesive properties against a Gram-positive and a Gram-negative bacterium. Such coatings are also capable of releasing antibacterial compounds in response to pH changes. Films were prepared by self-assembly of polymers at the surface. Our findings showed that zwitterionic micellar coronae introduced bacterial anti-adhesive property to the films, whereas pH-responsive micellar cores enabled release of an antibacterial agent from the surface at acidic pH. Considering the moderately acidic conditions around an infection site, such multilayers can be promising for the coating of implants/medical devices.